PNPP-1: The Issue of Nuclear Radiation and Waste - Dayrit, Fabian M. (Kasarinlan: Philippine Journal of Third World Studies; Vol 1 No 1 (1985), 2007)
The economics of nuclear power plant for the Philippines is highly problematic. The safety, waste management and technological manpower demands of Philippine Nuclear Power Plant-1, not to mention the uncertain nuclear fuel costs, will demand a heavy financial outlay.